FOREIGN AID TO UKRAINE AFTER 2014: VOLUMES, PROJECTS AND DONORS’ MOTIVATION - O. V. Shishkina (Vestnik MGIMO-Universiteta)
The article deals with assistance aid provided by the international donors to Ukraine. Author analyzes Ukrainian statistics on the issue – the projects registered between January 2014 and February 2018 by two Ukrainian ministries – the Ministry of Economic Development and Trade and the Ministry of Finance. Although incomplete, this data is considered assistance, which has reached Ukraine. The author names the overall volumes of international assistance to Ukraine, amounts offered in loans and grants and the major allocations of assistance. Proceeding from priority areas of aid, the author concludes on the donor’s motivations and their possible specific interests in Ukraine. Major Ukrainian donors – international financial organizations (IMF, IBRD, EIB, EBRD and KfW), as well as the European Union, the UN, Chernobyl Shelter Fund and donor states (the United States, Germany and Canada) have specific approaches towards assistance aid. While multilateral institutions tend to address the needs of Ukrainian economy by funding the reforms and infrastructure, donor states pay more attention to their long-term strategic and economic interests. They fund nuclear security and non-proliferation, support defense, law enforcement and border control agencies, encourage civil society and media development, consult agricultural sector and bilateral trade. States also ensure that national companies become contractors of their aid projects. Common motivation both for multilateral donors and states is to turn Ukraine into a western-like state with a transparent system of governance sensitive to foreign influence.